(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
Analytical and numerical studies have shown that multipolar vortices can emerge in two-dimensional flow due to azimuthal normal mode perturbations of shielded vortices. It has been found that mode 2 and 3 perturbations can lead to the formation of stable tripoles and quadrapoles, respectively, while higher order modes result in more complex unstable compound vortices. We have used the lattice Boltzmann method to simulate the effect of azimuthal perturbations on shielded vortices at moderate Reynolds numbers. We have found that azimuthal normal mode perturbations result in the formation of multipoles, which decay due to viscous dissipation. We could also observe that the outcome of such simulations is very sensitive to the displacement of perturbations above wavenumber-3 excitations, in spite of the significant viscosity we used.